Ethical issues in two parallel trials of personalised criteria for implantation of implantable cardioverter defibrillators for primary prevention: the PROFID project—a position paper. Issue 2 (14th July 2021) - Willems, Dick; Bak, Marieke; Tan, Hanno; Lindinger, Georg; Kocar, Ayca; Seperhi Shamloo, Alireza; Schmidt, Georg; Hindricks, Gerhard; Dagres, Nikolaos
Abstract : Aim: To discuss ethical issues related to a complex study (PROFID) involving the development of a new, partly artificial intelligence-based, prediction model to enable personalised decision-making about the implantation of an implantable cardioverter defibrillator (ICD) in postmyocardial infarction patients, and a parallel non-inferiority and superiority trial to test decision-making informed by that model. Method: The position expressed in this paper is based on an analysis of the PROFID trials using concepts from high-profile publications in the ethical literature. Results: We identify ethical issues related to the testing of the model in the treatment setting, and to both the superiority and the non-inferiority trial. We underline the need for ethical-empirical studies about these issues, also among patients, as a parallel to the actual trials. The number of ethics committees involved is an organisational, but also an ethical challenge. Conclusion: The PROFID trials, and probably other studies of similar scale and complexity, raise questions that deserve dedicated parallel ethics and social science research, but do not constitute a generic obstacle. A harmonisation procedure, comparable to the Voluntary Harmonization Procedure (VHP) for medication trials, could be needed for this type of trials.